THE SIGNIFICANCE OF BALNEOTHERAPY FOR THE REDUCTION OF PAIN IN ELDERLY PATIENTS WITH THE CERVICAL SYNDROME - Cvijanovic, Jelena; Devecerski, Gordana (HEALTH CARE, 2020)
Introduction/Aim: Neck pain is one of the most common musculoskeletal conditions, which is experienced by two thirds of world population at some stage in life. It can be associated with degenerative changes, psychosocial factors, sedentary way of life, reduced physical activity and stress. The aim of this study is to examine the significance of balneotherapy for the reduction of pain in elderly persons with moderately severe pain caused by cervical syndrome. Methods: Ten men and fifty-two women aged 61 to 80 years, who experienced a moderately severe pain caused by the cervical syndrome and who did not have contraindications for the application of balneotherapy and kinesitherapy, were included in this panel study. A Visual Analogue Scale (VAS) was used to measure the intensity of pain before and after balneotherapy and kinesitherapy. Results: There was no significant difference between men and women regarding age and propagation of cervical pain. After ten days of therapy, the pain stopped in around one-third of examinees, who experienced a moderately severe cervical pain and who used the thermal mineral bath with and without exercises. In every other examinee with the moderately severe intensity of cervical pain, this pain stopped after ten days of using thermal mineral water that reached ⅔ of the bathtub, and in one-third of examinees who used the thermal mineral pool and who exercised. A significantly better effect in pain elimination was achieved after the thermal mineral bath with water that filled ⅔ of the bathtub (p = 0.001) and the thermal mineral pool with exercises (p = 0.009) than after themal mineral bath with water that filled ½ of the bathtub. It was not determined whether there was a significant difference regarding the reduction of cervical pain after the application of thermal mineral bath with ⅔ of water in the bathtub and after the use of the thermo-mineral pool with exercises. Conclusion: Balneotherapy takes an important place in the reduction of pain in elderly persons with a moderately severe pain caused by the cervical syndrome. However, more detailed research is needed to explore the significance of balneotherapy and kinesitherapy for the reduction of pain caused by cervical syndrome, especially if population aging is taken into consideration.